Sensitivity Analysis of Wear on Metal-On-Metal Bearing Couples via Verification of Numeric and Analytic Methods - Alican Tuncay Alpkaya; Senay Mihcin (Hittite Journal of Science and Engineering)

(untitled)
Wear mechanism is important since it leads to revisions in Total Hip Replacement (THR) surgeries. Contact pressure plays an important role in wear mechanisms and needs to be investigated in detail to obtain more accurate wear predictions to understand the wear performance of the implant in the design stage. This study proposes a methodology for verification of contact pressure and pressure distribution via numeric and analytic methods to be used in wear calculations. Based on Hertz’s contact theory, the contact pressure and the contact area ae calculated in the analytical method. The results are compared to the numeric method’s results obtained from the finite element method. The linear and volumetric wear rates of bearing couples’ surfaces were estimated by Archard’s wear equation. The effect of design parameters on pressure such as head radius, cup thickness, material combination of bearing couples, coating film material, and film thickness are investigated in this study using the proposed methodology. The minimum error between the analytical and numerical results was 0.24% for 28 mm of head diameter, while the maximum error was 11.79 % for 48- mm of head diameter. The minimum contact pressure values were obtained from 48- mm of head radius at a half contact angle of 190 (degrees) in FEM and Hertz calculations, respectively. The maximum linear wear rate was calculated at 0.0026 mm/Mc at a 1- mm cup thickness, while minimum linear wear rate was 0.0022 mm/Mc at a 10- mm cup thickness in the numeric method. The maximum survival cycles of coating materials rate were 31847 cycles for the Stainless-steel coated cup with 500 μm of coating thickness, while the minimum cycles was 2359 cycles for the Ti64 coated cup surface with 100 μm of coating thickness. It is concluded that the most important design parameters are the cup thickness and the material combinations since they have a significant effect on the contact pressure and the contact area. This study provides a verification methodology for the parametric sensitivity analysis before experimental validations. The methodology utilized in this study could be utilized by designers while optimizing the design parameters to minimize the wear.